Escaping obsolescence? The shift from subject to skill based education in a South Korean international school. Issue 5 (3rd September 2018) - Oh, Hyun Joo S.
ABSTRACT: This paper interrogates how upper-class South Korean locals attending a newly established international school in the Songdo International Business District in South Korea, are socialized to both envisage and escape obsolescence. The stagnation of Songdo's population growth in the wake of the 2008 Global Financial Crisis, which altered many corporations' plans to relocate to this 'aerotropolis' remains key in subjects' theorizations of capitalism's failures. Acknowledging that we live under conditions of market volatility, administrators and faculty shift their pedagogical goals from subject to skill-based education. 'Resilience' is highly valued as a character trait drawing from emotional resources to operate in futures that cannot yet be imagined. Attempts to create desirable forms of human capital undergird the formation of educational experiences, conducive to producing twenty-first century global leaders, but they also generate uncertainty and reveal the complexity of maintaining privilege in competitive environments.